KEMAMPUAN PENALARAN DAN KOMUNIKASI MATEMATIS MAHASISWA: SLR DALAM PERSPEKTIF EPISTEMIK DAN DISKURSIF - Cita Dwi Rosita; Irmawati Liliana Kusuma Dewi; Asep Amam (Euclid, 2026)
Mathematical reasoning and mathematical communication are two fundamental dimensions of learning mathematics in higher education that are often investigated separately. This article aims to reconceptualize their relationship through an epistemic–discursive perspective, viewing reasoning and communication as mutually constitutive practices in undergraduate students’ mathematical activity. The study employs a systematic literature review of articles published in internationally reputable journals over the last decade that address mathematical reasoning, communication, argumentation, and discourse in higher education contexts. The synthesis was conducted using thematic synthesis enriched by theoretical analysis. The findings indicate that mathematical reasoning cannot be fully understood without considering the communicative dimension and the discursive norms that mediate it, while mathematical communication functions as a medium of thinking and meaning-making rather than merely a means of expression. Based on these findings, the article proposes an integrative conceptual framework that positions mathematical argumentation and epistemic norms as central mediators between students’ reasoning and communication. This study contributes theoretically by offering a reconceptualization of reasoning and communication that is relevant for research and teaching in undergraduate mathematics education.